EXPERT SYSTEM FOR DETECTING STRESS IN STUDENTS TAKING FINAL ASSIGNMENTS USING THE DEMPSTER SHAFER METHOD - Wulandari, Desika; Ramdhani Nugraha, Agus; Kartika Wibisono, Sony (ADVANCE INFORMATICS RESEARCH JOURNAL, 2025)
This study aims to address the stress problem often experienced by final year students, especially in the process of completing their final assignments or theses. The researchers designed an expert system application to help students identify their stress levels and provide appropriate management solutions. Using the Dempster-Shafer theory as the basis for calculating the confidence value, this application was developed using the Rapid Application Development (RAD) method and built as a web-based system using PHP and MySQL. The test results showed a stress diagnosis accuracy of 94%, which is categorized as "Very Good" based on the Mean Opinion Score (MOS). Suggestions for further development include exploring alternative methods such as confidence factors and Bayes' theorem, as well as developing a mobile-based application to increase accessibility. This application is expected to be an effective solution in overcoming stress-related challenges faced by final year students during the process of completing their final assignments.